Yeonpyeong : dealing with North Korea - Lee, Dongmin (2011)
North Korea's recent actions, including the intensification of the uranium-enrichment programme and the artillery bombardment on the Yeonpyeong Island has raised international concern. It is time that concrete measures are taken to deal with the Pyongyang regime to maintain stability in the region.